2013
DOI: 10.15517/rbt.v61i4.12806
|View full text |Cite
|
Sign up to set email alerts
|

Dinámica poblacional de <i>Donax denticulatus</i> (Bivalvia: Donacidae) en playa Carenero, costa sur oriental de Cuba

Abstract: Population dynamic of Donax denticulatus (Bivalvia: Donacidae) at Carenero Beach, Southeastern Cuba. Bivalve molluscs of Donax genus are a very important component of macro-invertebrate assemblages of sandy beaches, and some species are of commercial value in different countries. Although in Cuba Donax denticulatus is not a currently exploited species, the information concerning a stock assessment is a basic step for future use of this resource. With the aim to generate new data on this species structure, grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…According to these data, D. striatus from Las Balsas beach had higher growth performance than populations of other Donax species inhabiting the same climate region. These values match with other species of the same genus located in temperate zones, but that have reach longer shell sizes; this could be explained by the estimation method used in this study (Ocaña, Apín, & Cala, 2013). Growth estimates based on length-frequency data may be biased for tropical species which present continuous recruitment along the year (Sparre & Venema, 1997).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…According to these data, D. striatus from Las Balsas beach had higher growth performance than populations of other Donax species inhabiting the same climate region. These values match with other species of the same genus located in temperate zones, but that have reach longer shell sizes; this could be explained by the estimation method used in this study (Ocaña, Apín, & Cala, 2013). Growth estimates based on length-frequency data may be biased for tropical species which present continuous recruitment along the year (Sparre & Venema, 1997).…”
Section: Discussionsupporting
confidence: 68%
“…Secondary production of D. striatus is higher than the overall median estimated by Petracco, Cardoso, and Turra (2013) to bivalves of sandy beaches. High renewal rate matches with values of some tropical species according to Herrmann et al (2009), nevertheless is lower than P/B rate reported for D. incarnatus, D. spiculum (Ansell et al, 1978) and for D. denticulatus (Vélez et al, 1985;Ocaña et al, 2013). The rapid growth and high turnover rate of D. striatus suggest a rapid recovery of the population.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Proporción de individuos por componentes de la población (reclutas, jóvenes y adultos) por estrato (S1, S2 y S3) de Donax denticulatus en playa Levisa natural mortality (Le Moal, 1993;Defeo & Alava, 1995), no fluctuations of the population from Levisa Beach could be related to the season of our survey. Monthly size-class histograms showed that recruitment only occurred in April-May, and it is possible that this population has a reproduction period during March-May, as reported in Carenero Beach (Ocaña et al 2013) near Levisa, contrary to some other populations that showed continuous recruitment throughout the year (Wade, 1968;Vélez et al 1985;Marcano et al 2003). Nonetheless, more extensive sampling is needed in successive years to reveal the D. denticulatus recruitment pattern in Southeastern Cuba.…”
Section: Discussionmentioning
confidence: 79%
“…Shell morphometrics and population dynamics of D. denticulatus were analyzed in the Carenero Beach (Ocaña & Fernández, 2011;Ocaña et al 2013). Considering that D. denticulatus is a potential unexploited resource for fisheries, it is important to conduct further research in order to evaluate stocks on some beaches.…”
Section: Introductionmentioning
confidence: 99%